Isolation of Lipid Droplets from Cells by Density Gradient Centrifugation - Brasaemle, Dawn L. (Curr Protoc Cell Biol, 2016)
Lipid droplets are organelles found in most mammalian cells, as well as various plant tissues and yeast. They are composed of a core of neutral lipids surrounded by a membrane monolayer of phospholipids and cholesterol into which specific proteins are embedded. This unit provides protocols for isolating lipid droplets from mammalian cells by discontinuous density gradient centrifugation.